An overview of current developments in the study and practice of public administration - Reyes, Damilo R. (2001)
Globalization has served to reshape the topography of public administration dynamics, particularly in policymaking and service delivery systems. it has rendered public administration sensitive to the formation of administrative systems compatible with the demands and pressures of transnational interplay. Partnership has become an operative term and this has been recognized as a crucial component of governing. Conventional thinking in public administration has thus broadened. There had been significant initiatives made to draw attention to how bureaucracy and public administration must deal with the realities of governing in the face of an increasingly globalized and competitive milieu. This article provides a bird's eye view of the developments that have recently evolved in mainstream public administration thought. It aims to gather some of them for purposes of generating discourse in the Philippines. The article is a brief passing effort to inventory and highlight some of these ideas. - Reproduced.
Keywords: Public administration